Spelling errors in official letters in the Ciracas area East Jakarta - Sri Mulyani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is to describe spelling errors in the official letter in ciracas area, East Jakarta written since February ---- November 2017 while the method used in this research, that is descriptive qualitative. Data collection techniques by collecting six letters of service. After research on six official letters from the "Suci" Islamic Foundation, Al-Hidayah educational institutions, Adhiluhur Mahadika Foundation, Madrasah High School Mahadika, Fathurahman Mosque prosperity Council, and PT PLN in Ciracas region, resulted in erroneous spelling of Indonesian ( EBI) in total amounted to 32 findings relating to the writing of abbreviations amounted to 8 findings or 25%, the composite word writing amounted to 5 findings or 15.62%, the use of punctuation marks 9 findings or 28.12%, writing absorption element 2 findings or 6 , 25%, letter writing amounted to 4 finding or 4.12%, and word writing gamounted to 4 finding or 12.5%. From this finding, it was concluded that the bigges spelling use error in the official letter on the use punctuation is 28, 12%.